Autologous stem cell transplantation as frontline strategy for peripheral T-cell lymphoma: A single-centre experience. (February 2017) - Han, Xiao; Zhang, Wei; Zhou, Daobin; Ruan, Jing; Duan, Minghui; Zhu, Tienan; Li, Jian; Cai, Huacong; Cao, Xinxin; Ouyang, Mingqi
Objective: To determine the efficacy and prognosis of autologous hematopoietic stem cell transplantation (ASCT) as frontline treatment for peripheral T cell lymphoma (PTCL). Methods: Clinical data from 46 PTCL patients who achieved complete (CR) or partial remission (PR) after ASCT from October 1996 to July 2014 were analysed retrospectively. Results: Median patient age was 32 (range: 15–68) years. Disease types included PTCL, unspecified type, in 23 patients, anaplastic large cell lymphoma in eight, angioimmunoblastic lymphoma in eight, extranodal NK/T-cell lymphoma in five, and hepatosplenic T-cell lymphoma and enteropathy associated T-cell lymphoma in one each. Of these patients, 80% had Prognostic Index for Peripheral T-cell Lymphoma scores ≥1. Thirty-four patients had pre-transplantation CR and 12 had PR. Median follow up was 37 (6–176) months. The 5-year overall survival (OS) and progression-free survival (PFS) rates were 77.1% and 61.9%, respectively. Multivariate analysis showed that pre-transplantation CR was an independent risk factor for survival, and CR was more common than PR (OS 81% vs 59.3%; PFS 71.8% vs 17.8%). Conclusion: Frontline consolidation treatment with ASCT was associated with favourable outcomes in patients with PTCL. Pre-transplantation CR was a prognostic factor for survival, suggesting that ASCT may be favoured as front-line consolidation therapy after first complete remission.